Bioavailability pharmacokinetics and residues of marbofloxacin in normal and E.coli infected broiler chicken - El-Komy, Ashraf; Attia, Taha; Abd El Latif, Amera; Fathy, Hanem (International Journal of Pharmacology and Toxicology, 2016)
The pharmacokinetics of marbofloxacin was studied following a single intravenous, oral administration in normal broiler chickens and repeated oral administrations in normal and experimentally E.coli infected broiler chickens. The pharmacokinetic parameters following a single intravenous injection of 2 mg/kg b.wt., revealed that marbofloxacin obeyed a two compartments open model, distribution half-life (t0.5(α)) was 0.25±0.02 h, volume of distribution (Vdss) was 0.76±0.08 L/kg, elimination half-life (t0.5(β)) was 5.43±0.87 h and total body clearance (CLtot) was 0.09±0.002 l/kg/h. Following a single oral administration, marbofloxacin was rapidly and efficiently absorbed through gastrointestinal tract of chickens as the absorption half-life (t0.5 (ab): 0.62±0.02 h). Maximum serum concentration (Cmax) was 1.15±0.01 μg/ml, reached its maximum time (tmax) at 2.53±0.04 h, elimination half-life (t0.5 (el)) was 7.36±0.20 h indicating the tendency of chickens to eliminate marbofloxacin in slow rate. Oral bioavailability was 73.57± 1.90 % indicating good absorption of marbofloxacin after oral administration. Serum concentrations of marbofloxacin following repeated oral administration of 2 mg/kg b.wt. once daily for five consecutive days, peaked 2 hours after each oral dose with lower significant values recorded in experimentally infected broiler chickens than in normal ones. Tissues residues of marbofloxacin in slaughtered normal chickens was highly in those tissues lung, liver, and kidneys in chickens and the chicken must not be slaughtered before 3 days of stopping of drug administration. It was concluded that the in- vitro protein binding was 12.33±0.82%.